Evaluación del cumplimiento del plan operativo institucional del Hospital Regional de Loreto, periodo 2020 - Garcia Chuquipiondo, Maricielo (2023)
The main objective of this research work was to evaluate compliance with the Institutional Operational Plan of the Regional Hospital of Loreto for the achievement of institutional objectives, period 2020, for which the type of quantitative research with non-experimental design and type of research has been developed. descriptive transactional design; The study population consisted of 31 workers involved in the process, that is, officials, administrative personnel and health professionals of the Regional Hospital of Loreto, in addition to observing the management documents that correspond to the Institutional Operational Plan; It was concluded that the level of execution of the operational activity of the articulated nutritional program was not adequate due to the fact that the Loreto Regional Hospital became a Covid-19 Hospital, a fact that generated the suspension of care in external clinics due to provision of the Ministry of Health; however, the financial goals were executed at 98% motivated by regulatory provision that the financial balances of the programs could be executed to attend to the emergency by Covid-19 and in the other operational activities the physical and financial goals were met within the expected despite the restrictions arranged by the authorities motivated by the health emergency caused by COVID-19, highlighting the operational activity of the Prevention and Management of Secondary Health Conditions program in people with disabilities with a physical goal execution of 131%.